2020
DOI: 10.4155/fmc-2020-0052
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Adhesion in Fungal Pathogen Candida Albicans

Abstract: Fungal infections with increasing resistance to conventional therapies are a growing concern. Candida albicans is a major opportunistic yeast responsible for mucosal and invasive infections. Targeting the initial step of the infection process (i.e., C. albicans adhesion to the host cell) is a promising strategy. A wide variety of molecules can interfere with adhesion processes via an assortment of mechanisms. Herein, we focus on how small molecules disrupt biosynthesis of fungal cell wall components and membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 114 publications
2
25
0
Order By: Relevance
“…In our previous work [ 28 , 29 ] we established that compound 1 and derivatives were not toxic to C. albicans yeast cells at the concentrations used in the current study. Glycoconjugates 3 , featuring multivalent displays of the original lead compound 1 , along with tetra-β-triazolyl-galactoside 15 , were then evaluated for their anti-adhesive properties against C. albicans using several assays.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…In our previous work [ 28 , 29 ] we established that compound 1 and derivatives were not toxic to C. albicans yeast cells at the concentrations used in the current study. Glycoconjugates 3 , featuring multivalent displays of the original lead compound 1 , along with tetra-β-triazolyl-galactoside 15 , were then evaluated for their anti-adhesive properties against C. albicans using several assays.…”
Section: Resultsmentioning
confidence: 91%
“…In order to install lead compound 1 onto the alkyne-featuring scaffold 2 via the CuAAC reaction, it had to be functionalized with an azido group in a manner that would not compromise its interaction with target proteins in the C. albicans cell wall. Our previous work showed that functionalization of 5-aminobenzene position in compound 1 with a fluorescent label still allowed for the recognition of the digalactoside motifs and localization of the compound at the cell wall in C. albicans [ 28 ]. Thus, 5-amino-isophthalic acid was protected using tert -butoxycabonyl (Boc) anhydride, followed by reaction with propargylamine and TBTU to give compound 4 ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Candida albicans is an opportunistic pathogenic yeast and is the most prevalent cause of fungal infections worldwide, particularly in hospital-acquired infections. 35 37 The yeast is capable of causing a wide range of superficial and systemic infections in the immunocompromised patient, and there is now also growing concern for the coinfection of fungal pathogens in Covid-19 patients. 38 40 It is therefore extremely important that new treatments are developed for these fungal infections, some of which are now showing resistance to conventional antifungal therapies.…”
Section: Introductionmentioning
confidence: 99%